Bacteriocins of lactic acid bacteria as a hindering factor for biohydrogen production from cassava flour wastewater in a continuous multiple tube reactor. (25th May 2016) - Gomes, Simone Damasceno; Fuess, Lucas Tadeu; Mañunga, Tatiana; Feitosa de Lima Gomes, Paulo Clairmont; Zaiat, Marcelo
Abstract: Studies on fermentative systems applied to cassava processing wastewaters usually indicate favorable scenarios for biohydrogen (BioH2 ) production, considering the appreciable levels of carbohydrates found on such wastewaters. To assess the suitability of cassava flour wastewater (CFWW), a high-strength effluent from cassava flour industries, for BioH2 production, a continuous multiple tube reactor (CMTR) was applied in bench-scale assays. The CMTR is an innovative bioreactor configuration that promotes continuous biomass discharge and prevents the accumulation of solids in the long-term. Continuous experiments were conducted using raw and heat-treated CFWW, with and without nutrient supplementation. Although the carbohydrate conversion exceeded 90%, little to no hydrogen production was observed regardless of the feeding conditions. The poor performance of the CMTR could be associated with the presence of organic acids but is likely attributed primarily to bacteriocins Nisin A and Nisin Z in the CFWW, as an evidence of the presence of lactic acid bacteria. The type of cassava wastewater may severely affect hydrogen production; therefore, prior characterization of the CFWW influent is essential to determine its suitability for acidogenic systems. Highlights: An innovative reactor configuration was assessed for biohydrogen production. Raw and heat-treated cassava flour wastewater was used as substrate. Nutrient supplementation did not enhance hydrogen production. Hydrogen production was severely inhibited by metabolites found on the effluent. LC-MS/MS analyses identified the bacteriocins Nisin A and Nisin Z in the effluent.